Implementación de estrategias metodológicas y su impacto en el aprendizaje de matemáticas en los estudiantes de 3er. año de EGB de la Escuela de Educación Básica Víctor Mercantes 2023-2024 - Gutierrez Alava, Maykol Gabriel (2023)
The present case study addresses low academic performance as a common educational problem in the area of Mathematics, focused on the third year of the Víctor Mercantes School of Basic Education, in this instance a research process and information analysis is carried out to the subsequent design of new methodological strategies, focused on teaching methods. Based on this, the possibility of improving the academic performance of students in the aforementioned year is proposed. This study tries to see how feasible it is to implement a student-centered methodological proposal based on three methodological strategies (problem-based learning, case-based learning, depending on the institution's methodology, which is mainly based on experimentation. For this purpose, this work was based primarily on an interview directed at the teachers of said institution. Methodological strategies are important within the teaching-learning process of mathematics, because they tend to be essential for the intellectual development of children, since they Helps develop logical thinking.